Iron status in women of reproductive age in Morocco - Bouchra Mekkaoui; Nabila Auajjar; Abdelhakim Yahyane; Laila El Ammari; Salwa Labzizi; Anouar Talouizte; Hasnae Gamih; Hassan Aguenaou; Kaoutar Benjeddou; Khalid El Kari (Roczniki Panstwowego Zakladu Higieny, 2025)
Background Women of reproductive age (WRA) are one of the vulnerable population mostly impacted by anemia and iron deficiency (ID) worldwide.